Prednisolone-loaded coatable polyvinyl alcohol/alginate hydrogel for the treatment of atopic dermatitis. Issue 13 (2nd September 2018) - Lee, Hye Ri; Kim, Tae Ho; Oh, Se Heang; Lee, Jin Ho
Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease resulting pruritic, erythema, edema, excoriation, and thickening of the skin, and thus leads to significant impairment in the patient's life. The objective of this study is to develop a steroid drug [prednisolone (PS)]-loaded coatable hydrogel for the treatment of AD. PS-loaded hydrogel was composed of PVA entrapped in mildly crosslinked alginate (PS-loaded PVA/ALG hydrogel). The PS concentration to be loaded in the hydrogel that takes AD efficacy without cell necrosis was determined from the cytotoxicity test using human dermal fibroblasts. The in vivo therapeutic effects for AD of the PS-loaded PVA/ALG hydrogel were evaluated using 2, 4-dinitrochlorobenzene (DNCB)-induced AD Balb/c mouse model. The PS-loaded hydrogel has an appropriate viscosity for easy application and provides moisturizing effect on the skin, as well as anti-inflammatory effect by the sustained drug release for effective AD treatment. From the animal study, the PS-loaded PVA/ALG hydrogel showed effective suppressions of various AD symptoms such as ear edema, pruritus, high IgE levels, epidermal swelling, and mast cell infiltration. Our findings suggest that the PS-loaded coatable PVA/ALG hydrogel may be a promising therapeutic system for the treatment of AD. Abstract :